Antioxidant, starch-digesting enzymes inhibitory, and pasting properties of elite yellow-fleshed cassava genotypes - Kareem, B.; Irondi, E.A.; Alamu, Emmanuel Oladeji; Ajani, E.O.; Abass, A.; Parkes, Elizabeth Y.; Maziya-Dixon, Busie (Frontiers Media, 2023)
Biofortification of cassava roots has improved its health benefits by raising the quantity and bioavailability of bioactive compounds, particularly carotenoids. This study analyzed the bioactive constituents (carotenoids, tannins, total phenolics, and flavonoids), antioxidant, starch-digesting enzymes (a-amylase and a-glucosidase) inhibitory and pasting properties of flours of 18 elite yellow-fleshed cassava genotypes grown at the International Institute of Tropical Agriculture, Ibadan, using standard laboratory methods. Generally, the concentrations of the bioactive constituents (9-cis- -carotene, 13-cis- -carotene, all trans- -carotene, total -carotene, total carotenoids, tannins, total phenolics, and total flavonoids) of the di􀀀erent cassava genotypes varied. The antioxidant activity varied significantly among the di􀀀erent cassava genotypes, with IITA-TMS-IBA183001 having the highest reducing power (2.59 GAE mg/g) and most potent DPPH· scavenging ability (SC50: 14.56 mg/mL). However, the starch-hydrolysing enzymes (alpha-amylase and alpha-glucosidase) inhibitory and the pasting properties of the di􀀀erent genotypes were generally comparable. Total carotenoids content significantly correlated with the DPPH· SC50 (r = −0.495), while total phenolics content correlated with ABTS·+(r = 0.839) and DPPH· SC50 (r = −0.870). Also, tannins content significantly correlated with ABTS·+ (r = 0.553), while total flavonoids content was significantly correlated with a-amylase IC50 (r = −0.532). These findings suggest the potential of flours of the 18 elite yellow-fleshed cassava genotypes to serve as important dietary sources of antioxidants and starch-hydrolysing enzyme inhibitors, which may be beneficial in oxidative stress and postprandial hyperglycaemic conditions.